HUBUNGAN ANTARA ANEMIA IBU HAMIL TRIMESTER III DENGAN PERDARAHAN PASCA PERSALINAN DI RSUD SUNAN KALIJAGA DEMAK PERIODE JANUARI - DESEMBER 2024 (Studi Observasional Analitik) - Muhammad Khalid Fathoni; Masyhudi (Jurnal Riset Multidisiplin Edukasi, 2026)
Postpartum hemorrhage is one of the leading causes of maternal mortality. Anemia in pregnant women, particularly during the third trimester, is recognized as an important risk factor for postpartum hemorrhage through impaired uterine contractility caused by decreased tissue oxygenation. This study aimed to determine the association between third-trimester maternal anemia and the occurrence of postpartum hemorrhage at RSUD Sunan Kalijaga Demak during the period of January–December 2024. This study employed an analytical observational design with a case–control approach. The sample consisted of 30 third-trimester pregnant women who delivered, including 15 women with postpartum hemorrhage as the case group and 15 women without postpartum hemorrhage as the control group. Data were obtained from medical records, including third-trimester hemoglobin levels, postpartum hemorrhage incidence, as well as demographic characteristics and obstetric history. Data analysis was performed using the Chi-square test or Fisher’s Exact Test with a significance level of α = 0.05, along with the calculation of Odds Ratio (OR) and 95% Confidence Interval (CI). The results showed a statistically significant association between third-trimester maternal anemia and postpartum hemorrhage (p = 0.008). Pregnant women with anemia had a 13-fold higher risk of developing postpartum hemorrhage compared to non-anemic women (OR = 13.00; 95% CI: 2.07–81.48). In conclusion, there is a significant association between third-trimester maternal anemia and the occurrence of postpartum hemorrhage. Strengthening the prevention and management of anemia during pregnancy is essential to reduce the risk of postpartum hemorrhage.